Experimental Validation on a New Valve Core of the Throttle Valve in Managed Pressure Drilling. (17th June 2014) - Wang, G. R.; Tao, S. Y.; Liu, Q. Y.; Fu, Y. K.; Zhu, H.; Chu, F.
Abstract : This paper is concerned with experimental investigation of the linear opening-pressure drop (L − Δ P ) relationship of new valve core in managed pressure drilling (MPD). Based on the linear L − Δ P relationship in theoretical results, the actual L − Δ P relationships are obtained by testing the flow rate, displacement of the valve core, and pressures at the import and export. Under all three working conditions, the theoretical L − Δ P relationship almost agrees with the experimental result, and the accuracy of the theoretical design is validated. In addition, the flow coefficient (C v ) is also tested in the experimental process to judge the throttling characteristics of the new valve core and the proper working conditions.